The firehouse mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York : Scholastic, 1997)
The Alden children draw upon their resourcefulness to save the neighborhood firehouse from being torn down, while they also face a series of mysterious incidents connected with it.
640
Accelerated Reader AR